Self-care interventions for legal and safe abortions: lessons learned from a woman-centered approach to sexual and reproductive healthcare in Uruguay - Cecilia Stapff; Lucía Gómez Garbero; Rodolfo Gómez Ponce de León; Leonel Briozzo; Antonella Lavelanet; Manjulaa Narasimhan (The Lancet Regional Health. Americas)
Summary: Problem: In the 1990s, almost 40% of maternal deaths in Uruguay were caused by unsafe abortions. Approach: A harm reduction model implemented in Uruguay, which addressed the risks associated with unsafe abortion practices by promoting and supporting the self-management of medical abortions by women in their homes, encouraged women’s autonomy. Local setting: Since 2005, an accelerated decrease in maternal mortality has been recorded in Uruguay, coinciding with the implementation of two major actions: a harm reduction approach with active promotion of self-care through self-management of medical abortions; and in 2012, a change in legislation, which made abortion legal within sexual and reproductive health facilities when requested by women up to 12 weeks of pregnancy or later for specific indications. Relevant changes: This example demonstrates that progress in public policies is possible through the combined efforts of civil society, healthcare professionals and policy makers. The initiative expanded the entry points to the healthcare system while strengthening women’s autonomy. Lessons learned: Increased access to self-care interventions for SRH contributed to advancing achievement of universal health coverage and the highest, most attainable standards of health. Funding: The authors have no financial relationships relevant to this article to disclose.